APPLICATION OF THE PROJECT BASED LEARNING MODEL ON HISTORICAL STORY TEXT MATERIALS FOR CLASS XII SMA LPP–UMI - Nur Hikma; muliadi muliadi; Nur Fathana Mazhud (Citra Dharma Cindekia, 2022)
Writing skill is one of the most important language skills to be taught to students. To be able to practice writing skills, the teacher should use the right learning model. The right learning model to practice writing skills is Project Based Learning. Project Based Learning is a learning model that involves students in a project activity so that learning becomes more active, meaningful, and fun. The purpose of this study was to improve the writing skills of class XII students of SMA LPP-UMI on historical story text material through a project based learning model. This research is a type of classroom action research. Data collection techniques used are observation, questionnaires, and documentation. The results showed that there was an increase in the average results of historical story texts from 61 in the pre-cycle to 68 in the first cycle, and 79 in the second session with the percentage of students who finished learning 91.10%. Therefore, it can be concluded that the project learning model can improve students' writing skills on historical story text material.